RELASI ANTARA SENI DENGAN TEOLOGI KRISTEN - Utomo, Yunatan Krisno (Sekolah Tinggi Teologi Kristus Alfa Omega, 2018)
Art is often viewed as a worldly thing connected with worldly luxuries and pleasures. In response to the use of this art, it is no wonder that among mainstream theologians there is a dichotomy between the spiritual and the earthly or the holy and the secular. The effect is that many Christians close themselves to the things they regard as 'worldly' in the social life of society, and they live alone isolated in their holiness. This study discusses that art is God's creation, so the presence of art should be able to help humanity establish its existence as a creature and be able to help human beings become closer to God.